Ferritin H Deficiency in Myeloid Compartments Dysregulates Host Energy Metabolism and Increases Susceptibility to Mycobacterium tuberculosis Infection - Reddy, Vineel P.; Chinta, Krishna C.; Saini, Vikram; Glasgow, Joel N.; Hull, Travis D.; Traylor, Amie; Rey-Stolle, Fernanda; Soares, Miguel P.; Madansein, Rajhmun; Rahman, Md Aejazur; Barbas, Coral; Nargan, Kievershen; et al. (Frontiers in Immunology, 2018)
Iron is an essential factor for the growth and virulence of Mycobacterium tuberculosis (Mtb). However, little is known about the mechanisms by which the host controls iron availability during infection. Since ferritin heavy chain (FtH) is a major intracellular source of reserve iron in the host, we hypothesized that the lack of FtH would cause dysregulated iron homeostasis to exacerbate TB disease. Therefore, we used knockout mice lacking FtH in myeloid-derived cell populations to study Mtb disease progression. We found that FtH plays a critical role in protecting mice against Mtb, as evidenced by increased organ burden, extrapulmonary dissemination and decreased survival in Fth-/- mice. Flow cytometry analysis showed that reduced levels of FtH contribute to an excessive inflammatory response to exacerbate disease. Extracellular flux analysis showed that FtH is essential for maintaining bioenergetic homeostasis through oxidative phosphorylation. In support of these findings, RNAseq and mass spectrometry analyses demonstrated an essential role for FtH in mitochondrial function and maintenance of central intermediary metabolism in vivo. Further, we show that FtH deficiency leads to iron dysregulation through the hepcidin-ferroportin axis during infection. To assess the clinical significance of our animal studies, we performed a clinicopathological analysis of iron distribution within human TB lung tissue and showed that Mtb severely disrupts iron homeostasis in distinct microanatomic locations of the human lung. We identified hemorrhage as a major source of metabolically inert iron deposition. Importantly, we observed increased iron levels in human TB lung tissue compared to healthy tissue. Overall, these findings advance our understanding of the link between iron-dependent energy metabolism and immunity and provide new insight into iron distribution within the spectrum of human pulmonary TB. These metabolic mechanisms could serve as the foundation for novel host-directed strategies.